Is The Compressive Nail Method Capable of Accelerating Bone Union in Patients with Femoral Shaft Fracture? - Turhan, Sadullah (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
We aimed to evaluate the effectiveness of compression by assessing finite element analysis with clinical and radiological evaluation of patients undergoing compressive and conventional intramedullary nailing for femur shaft fractures.We retrospectively examined a total of 162 patients from November 2012 to August 2019. The patients were divided into Group 1 (n = 79) in which the conventional intramedullary nailing was used, Group 2 (n = 42) in which 1.0-mm compressive nails were used, and Group 3 (n = 41) in which 1.5-mm compressive nails were used. Group 2 (n = 42) with 1.0-mm compressive nails, and Group 3 (n = 41) with 1.5-mm compressive nails used. The mean follow-up period was 14.3 ± 4.2 (12–22) months for Group 1, 15.4 ± 5.2 (13–26) months for Group 2, and 14.2 ± 5.2 (13–24) months for Group 3.The mean union period and functional score were calculated as 13.6 ± 2.6 months (12–17 months) and 79.4, respectively, in Group 1, which is a good degree result. The mean union period and functional score were calculated as 12.2 ± 2.8 months (11–17 months) and 85, respectively, in Group 2, which is excellent. Lastly, the mean union period and functional score were calculated as 11.1 ± 2.5 months (10–19 months) and 86, respectively, in Group 3, (p < 0.001) which is also excellent. In Group 1, union was observed in three cases. In Group 2, union delay was observed in one case, whereas in Group 3, union was observed in all cases.Compression of femur shaft fractures speeds up bone healing and improves functional scores in adult femur shaft fractures, and compression can the fracture union period. Finite element analysis showed that there was no statistically significant difference between the compression amounts of 1.5 mm and 1.0 mm, but the effect of compression on bone union.
Keywords: intramedullary nail; compression; femur shaft fracture; union